2015
DOI: 10.1080/15384047.2015.1071738
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate sensitizes ovarian cancer cells to cisplatin by downregulating RAD51

Abstract: Artesunate, a semi-synthetic derivative of arteminisin originally developed for the treatment of malaria, has recently been shown to possess antitumor properties. One of the cytotoxic effects of artesunate on cancer cells is mediated by induction of oxidative stress and DNA double-strand breaks (DSBs). We report here that in addition to inducing oxidative stress and DSBs, artesunate can also downregulate RAD51 and impair DSB repair in ovarian cancer cells. We observed that the formation of RAD51 foci and homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 24 publications
7
46
1
1
Order By: Relevance
“…Thus, mitochondrial apoptosis occurs from the iron-dependent generation of cytotoxic oxidative stress [14], [15], [16], [17]. Artesunate also induces oxidative DNA damage, sustained DNA double-strand breaks, and the damage response in cancer cells [18], [19], [20]. These effects were clearly observed in cisplatin-sensitive and -resistant HNC cells in our study.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Thus, mitochondrial apoptosis occurs from the iron-dependent generation of cytotoxic oxidative stress [14], [15], [16], [17]. Artesunate also induces oxidative DNA damage, sustained DNA double-strand breaks, and the damage response in cancer cells [18], [19], [20]. These effects were clearly observed in cisplatin-sensitive and -resistant HNC cells in our study.…”
Section: Discussionsupporting
confidence: 61%
“…Artemisinins enhanced anticancer toxicity by utilizing ferrous iron to generate radicals that could kill cancer cells [14], [15]. Artesunate also induces lysosomal ROS-mediated mitochondrial apoptosis and targets the DNA damage and repair systems in conventional chemotherapeutic drug-resistant cancer cells [16], [17], [18], [19], [20]. Furthermore, a recent report suggested that artesunate induced iron-dependent, ROS-producing mitochondrial stress and non-caspase apoptosis [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARS increased significantly the incidence rates of MN containing both whole chromosomes and centric fragments, demonstrating its ability to act by means of aneugenic and clastogenic events. ARS is known to induce oxidative DNA damage and DNA double‐strand breaks in healthy and cancer cells, and such effects have been widely associated with an increase of ROS levels (Berdelle et al, ; Li et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of cancer cell lines were observed to respond to ARS by decreasing cell viability and increasing cell death (Greenshields, Shepherd, & Hoskin, ; Li et al, ; Pang, Qin, Wu, Wang, & Chen, ; Roh, Kim, Jang, & Shin, ). Similarly, incubation with ARS led to oxidative DNA damage, induction of DNA double‐strand breaks and increase of micronuclei (MN) frequency in both cancer cell lines and normal cells, including human lymphocytes (Aquino et al, ; Aquino, Ferreira, & Luis, ; Berdelle, Nikolova, Quiros, Efferth, & Kaina, ; Li et al, ; Mota et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%